Journey through self: design of contemplative spaces inspired from the philosophy and lyrics of Fakir Lalon Shah of Kushtia, Bangladesh - Ahmed, Syeda Tahmina (Department of Architecture, BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2013.